Dinamika Kesejahteraan Psikologis Remaja di Jawa Timur - Dhita Werdhikaning Tyas Asih,; Sri Wahyuni,; Nurul Hofifah,; Mohammad Agil Agustinu,; Junaidi Romadhon,; Ditenta Kurnia Tasya,; Ari Khusumadewi, (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2024)
Adolescents' psychological well-being is influenced by several factors, namely age, gender and parents' work. The aim of this research was to determine the dynamics of adolescent psychological well-being in East Java. This research is a quantitative descriptive study. Data collection was carried out through a survey using a research instrument in the form of a scale of adolescent psychological well-being which was distributed via Google Form. The population studied were teenagers aged 12-18 years who were currently attending junior high and high school in East Java. The sample was chosen randomly using a random sampling technique, with a total of 413 respondents. The results of this research show that the psychological well-being of teenagers in East Java in the 12-18 year age range is generally quite good, even in the high category. There is no significant difference in psychological well-being between male and female adolescents.In general, psychological well-being also tends to be high in various age ranges, with the peak occurring at age 17 years. In the context of socio-economic factors, the psychological well-being of adolescents is also relatively high, although adolescents with socio-economic backgrounds whose parents earn below the Minimum Wage (UMR) have a higher level of psychological well-being than those who earn above the minimum wage.